2014
DOI: 10.4314/ijbcs.v8i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content and heritability of resistance in four hybrid populations of <i>Theobroma cacao</i> L. after leaves inoculation with <i>Phytophthora megakarya</i> Bras. et Grif

Abstract: Cocoa is cultivated in Cameroon for its broad beans. The commercialization of cocoa seeds constitutes a major source of income to farmers. Nevertheless, cacao black pod disease caused by Phytophthora megakarya is responsible of about 80% of cocoa production loss in Cameroon without any protection method. To assess the resistance of cocoa plants against this pathogen, necrotic lesions and phenolic content were conducted on 3 clones (SNK16, ICS40, Sca12) and their progenies (families F40, F12, F20 and F25) after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
6
7
0
1
Order By: Relevance
“…This could be due to genetic incompatibility between clones and also the period of pollination. This result is similar to those found by Mossu (1990) and Ondobo et al (2014).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This could be due to genetic incompatibility between clones and also the period of pollination. This result is similar to those found by Mossu (1990) and Ondobo et al (2014).…”
Section: Discussionsupporting
confidence: 82%
“…This result is in agreement with the findings of Nyasse (1997). from the leaf disc test done in the laboratory, Efombagn et al (2011) on pods in field, Djocgoue et al (2010) and Ondobo et al (2014) on the leaves attached to the plant in nursery. There were significant (P<0.05) differences in the necrosis length of susceptible SCA 12 and SNK 16 as compared to T 79/501, T 79/467 and SNK 413.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the different responses of cocoa hybrids suggested that there could be an additive and dominant gene effect in the transmission of character [12] [21] [22] [23]. In the same way, a vast genetic variability for black pod resistance has also been reported in cocoa [9][14] [24].In our studies, the levels of tolerance of cocoa could be identified using any Phytophthora species. These findings are in agreement with results reported bysome authors [14][25] [26], who showed that the use of the most aggressive species of P. megakarya isolates could lead to the identification of useful levels of resistance against the pathogens.…”
Section: Discussionmentioning
confidence: 55%
“…Beberapa karakter komponen buah kakao, yang meliputi ukuran buah (pod), biji, kulit buah, dan pulpa, berhubungan langsung dengan produktivitas tanaman serta ketahanan terhadap hama penggerek buah (PBK) (Susilo, Mangoendidjojo, Witjaksono, Sulistyowati, & Mawardi, 2009;Wijaya, Prawoto, & Ihromi, 2009;Asrul, Agus, Daryati, & Mollah, 2012;Limbongan, 2012;Pertiwi, Asrul, & Baja, 2013;Susilo, Mawardi, Witjaksono, & Mangoendidjojo, 2015) dan penyakit busuk buah Ondobo et al, 2014;Simo et al, 2014) .…”
Section: Pendahuluanunclassified